Sosialisasi Potensi BADAN USAHA MILIK DESA (BUMDes) Makmur Untuk Meningkatkan Pemberdayaan Perekonomian Desa Bojong Gede - Santi Octavia (Jurnal Abdimas Ekonomi dan Bisnis, 2022)
The establishment of Village BUM is intended as an effort to accommodate all activities in theeconomic sector and/or public services managed by the Village and/or inter-Villagecooperation. Villages can establish Village-Owned Enterprises called Village BUM which aremanaged with the spirit of family and cooperation. Businesses that can be run by Village BUMare businesses in the economic sector or public services in accordance with the provisions oflaws and regulations. The establishment of Village BUM was agreed upon through villagedeliberations and stipulated by village regulations. This Empowerment activity aims to increasethe potential of Bumdes Makmur which is located in Bojong Gede Village - Bogor Regency,West Java. Based on a preliminary survey of conditions in Bojong Gede Village, lowinformation about the existence of Bumdes was identified. The public in general does not knowmuch, even though the condition of the majority of people working as farmers, traders andcraftsmen certainly needs a village institution that is able to accommodate the potential of thecommunity and the natural potential of the village in order to become a new source of incomefor the community. Empowerment activities provided in the form of socialization anddiscussion. Keywords: Village-Owned Enterprises, Economic Sector, Public Services